Studies on the Effect of Hybridization Between Eucalyptus citriodora and Eucalyptus torelliana - Kapoor, M. L.; Sharma, V. K. (Indian Forester, 1983)
Reciprocal hybrids between E. citriodora and E. torelliano belonging to subgenus Corymbia displayed superior growth. Hybridization evolved desired recombinations in respect or dense crown, aroma and resistance to fungus (Cylindrocladium quiqueseptaum) besides some intermediate characteristics. The two species through hybridization seem to have released a new spectrum of variation for making useful seleclions. Marker characters such as presence or absence of lignotubers and the shape of the leaf were used as diagnostic featurcs for detection of FI hybrids in the nursery. Aroma of crushed leaves proved to be a very handy method for detection of FI hybrids In the field. The results and the scope of the hybrids are discussed. In the papers The effect of hybridization between the two species manifests genetic manipulations.